Al-qiyam at tarbawiyyah fi sûrati maryam al âyah 16-21 fi tafsîri “fi dzilâli al-qur’ân li sayyid qutb - Agus Budiman; Rumbiati Rumbiati (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
The Quran is the source of education that contains the doctrine, worship, wisdom, literature, stories, advice, guidance and so on. Sayyed Qutb in his interpretation in the shadows of the Qur’an,